Chilling injury of large cardamom (Amomum subulatum Roxb.) in high altitudes of Sikkim and Darjeeling, India - A K Biswas, M R Sudharshan, K A Saju, T N Deka, U Gupta, (Journal of Spices and Aromatic Crops, 2012)
Manifestations of cold temperature damage on large cardamom (Amomum subulatum Roxb.) was monitored at Pangthang (2160 m MSL), East Sikkim during the winter seasons (October–March) of 2006–10. Damage to plant tissues, mainly leaves, occurred during prolonged cold wave conditions (below 6oC) that prevailed during December–February. Tiny pin prick like water soaked lesions appeared on the lamina, coalescing to form a large patch that died and turned pale brownish and served as infection court for fungal pathogens. Extreme frosting on leaves was more common in exposed areas without shade trees.